Numerical analysis of an enhanced cooling rate cryopreservation process in a biological tissue. (April 2019) - Sukumar, S.; Kar, S.P.
Abstract: Cryopreservation is the method of preservation of biological tissues for future references without causing significant damages to their physical and functional properties. This can be done by exposing them to very low cryogenic temperature that involves a greater heat removal rate. A two dimensional numerical model is developed to study the temperature distribution, cooling rate attained and movement of the freezing front during the cryopreservation process. The Pennes Bio-heat model is used for current study. The Finite Volume Method is employed for discretization of the governing differential equations while the Tri-Diagonal Matrix Algorithm is used to solve the discretized algebraic equations to find temperature distribution inside the domain. The Enthalpy-Porosity method is used to track the solid-liquid interfaces during the freezing process. The current model is first validated with the result of the existing literature. In the present work, freezing of tissue is done from one and two sides in two separate cases and the resulting temperature distribution inside the tissue and cooling rate in the two cases are compared. It is found that the freezing rate of tissue is enhanced about two times when it is freezed from two sides as compared to freezing from single side. Further, it is observed that a lower value of blood perfusion rate causes a lower value of the final temperature of the tissue after freezing. Thus, it can be concluded that the tissue with high blood perfusion rate is to be freezed in a lower cooling medium temperature. In the present condition, metabolic heat generation plays no significant role in the temperature distribution inside the healthy tissue. Highlights: A two dimensional numerical model is developed to study the cryopreservation in biological tissue. Pennes Bio-heat model is used for current study. The freezing is done from two sides of the tissue by which the cooling rate is enhanced and the total freezing time is reduced which is the essential requirement of the cryopreservation process. With increase in blood perfusion rate, the cooling rate reduces which necessitates the application of lower cryopreservation temperature for freezing of biological tissues with higher blood perfusion rates. Metabolic heat generation inside the biological tissue has a negligible role to play in the freezing of biological tissue.